Development of collision avoidance system for multiple autonomous mobile robots - Hou Y.C.; Mohamed Sahari K.S.; Weng L.Y.; Foo H.K.; Abd Rahman N.A.; Atikah N.A.; Homod R.Z. (SAGE Publications Inc., 2023)
Agricultural robots; Collision avoidance; Computer software; Data communication equipment; Highway accidents; Robots; Safety devices; Vehicle to vehicle communications; Autonomous Mobile Robot; Collision avoidance systems; Collision scenarios; Comprehensive comparisons; Crossing intersections; Experimental testing; Inter-robot communication; Rear-end collisions; Autonomous vehicles